IKLIM ORGANISASI, USIA DAN MASA KERJA SEBAGAI PREDIKTOR SUBJECTIVE WELL-BEING GURU SMP SWASTA X DI SURABAYA - Idha Rahayuningsih (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: Teachers' subjective well-being is influenced by the environment and situation within the organization. Objective: The purpose of this study was to determine the effect of organizational climate, age and length of service on subjective well-being of teachers at Private Junior High School X in Surabaya. Method: The study used a quantitative correlational-predictive approach. The sample of the study was 40 teachers at Private Junior High School X in Surabaya. The researcher developed a Likert scale to measure subjective well-being based on Diener (1984, 1993) and organizational climate based on Litwin and Stringer (1965). Result: Logical validity testing was carried out by expert opinion for both scales. On the subjective well-being scale, the r value ranged from 0.273 - 0.66 and the cronbach alpha reliability coefficient = 0.865. On the r value scale, the r value ranged from 0.804 - 0.825 while the coefficient was 0.822 reliability. F = 15.204 and p = 0.001 < 0.05 indicate that the regression equation model Y = 42.591 + 0.598.X1 + 0.643.X2 + 1.055.X3 is a goodness of fit to predict subjective well-being through organizational climate, age and tenure. Conclution: R² = 0.559, indicates that 55.9% of the subjective well-being variance can be explained simultaneously by changes in organizational climate, age and tenure while 44.1% is explained by other variables. The results of the study also show that partially organizational climate, age and tenure have a positive and significant effect on subjective well-being.